Forest Products: annual market review 2011-2012 - United Nations Economic Commission for Europe (UNECE).; Food and Agriculture Organization of the United Nations (FAO) (Geneva: United Nations, 2012)
The UNECE/FAO Forest Products Annual Market Review, 2011-2012 provides general and statistical information on forest products markets and related policies in the UN Economic Commission for Europe region (Europe, North America and the Commonwealth of Independent States). The Review begins with an overview chapter, followed by description of the macroeconomic situation, Next it includes an analysis of government and industriy policies affecting forest product markets. Five chapters are based on annual country-supplied statistics, describing: wood raw materials; sawn softwood;sawn hardwood ; wood-based panels; and paper, paperboard and woodpulp. Additional chapters discuss markets for wood energy, certified forest products, value-added wood products, forest carbon, and innovative wood products. Tables and graphs provided throughout the text present summary information. Supplementary statistical table may be found on the UNECE Timber Committee and FAO European Forestry Commission website.
Keywords: Forest Products; Timber Trade; Sustainable Forestry; Forestry Statistics